2020
DOI: 10.1017/s0967199420000490
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa morphology changes during reproduction and first observation of acrosomal contact in two dioecious species of Macrobiotidae (Tardigrada: Eutardigrada)

Abstract: Summary Mating behaviours for two species of dioecious eutardigrades: a strain of Paramacrobiotus sp. and Macrobiotus shonaicus (Stec et al., 2018) have been recorded previously, and observations have indicated that spermatozoa of both species are first released into the environment, then swim through the cloaca of the females and into the spermatheca. The fusion of gamete nuclei has not yet occurred in a laid egg. Therefore, it has been suggested that fertilization is completed externally as the egg is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…than in M. shonaicus, suggesting that the longer heads and tails of Paramacrobiotus sp. spermatozoa enhanced their movement [14]. It has been con rmed that the morphology and motility of spermatozoa work in cooperation during swimming [28].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…than in M. shonaicus, suggesting that the longer heads and tails of Paramacrobiotus sp. spermatozoa enhanced their movement [14]. It has been con rmed that the morphology and motility of spermatozoa work in cooperation during swimming [28].…”
Section: Discussionmentioning
confidence: 96%
“…Generally, the shapes of gametes should have some functional signi cance for e cient and certain reproduction. A previous study hinted at the existence of gamete morphological interference at the phase of fertilization in some species [14]. In addition, the exible and extraordinarily long acrosome has the potential to facilitate aggregation on the egg surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are currently detailed descriptions of sexual interaction for four gonochoristic species, representing two eutardigrade families (reviewed in Sugiura & Matsumoto, 2021c ). These studies all point to a key role of semiochemicals in male and/or ejaculate attraction, and of female behavior in ejaculate intake (Bartel & Hohberg, 2020 ; Bingemer et al, 2016 ; Sugiura et al, 2019 ; Sugiura & Matsumoto, 2021a , 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, observations of mating behaviours have revealed that the spermatozoa of the two species are rst ejaculated into the environment, after which they swim to the mating female and are stored in her spermatheca; then, oviposition occurs [13,15]. The morphologies of the spermatozoa have been well reported not only in these two species but also in other species belonging to the same family, Macrobiotidae [10,14,16,17,18,19,20]. Reports have demonstrated that the spermatozoa have a tail, an in ated or rod-shaped midpiece, a coiled nucleus and an acrosome.…”
Section: Introductionmentioning
confidence: 99%